Drawing the Greek vase - Meyer, Hans-Caspar; Petsalē-Diomēdē, Alexia (Oxford University Press, 2023)
How have two-dimensional images of ancient Greek vases shaped modern perceptions of these artefacts and of the classical past? This is a scholarly volume devoted to the exploration of drawings, prints, and photographs of Greek vases in modernity, and traces the ways artists have depicted Greek vases in a range of styles and contexts.
Also issued in print: 2023. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on June 23, 2023)
Keywords: Konferenzschrift -- 2015 -- Oxford